2023
DOI: 10.3390/ph16030416
|View full text |Cite
|
Sign up to set email alerts
|

Individual Treatment Trials—Do Experts Know and Use This Option to Improve the Treatability of Mucopolysaccharidosis?

Abstract: Mucopolysaccharidoses (MPS) are a group of rare, heterogeneous, lysosomal storage disorders. Patients show a broad spectrum of clinical features with a substantial unmet medical need. Individual treatment trials (ITTs) might be a valid, time- and cost-efficient way to facilitate personalized medicine in the sense of drug repurposing in MPS. However, this treatment option has so far hardly been used—at least hardly been reported or published. Therefore, we aimed to investigate the awareness and utilization of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As many immunomodulatory drugs are market-approved for other indications, ITTs combined with these are an obvious and time-efficient option to improve the treatability of MPS [ 20 , 21 ]. Drug repurposing is an EMA-recommended [ 27 ], highly personalizable [ 68 ] option to improve treatability in rare disorders [ 11 , 12 , 13 ], which is still underutilized, and only a few MPS centers make use of this, as shown by us previously [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As many immunomodulatory drugs are market-approved for other indications, ITTs combined with these are an obvious and time-efficient option to improve the treatability of MPS [ 20 , 21 ]. Drug repurposing is an EMA-recommended [ 27 ], highly personalizable [ 68 ] option to improve treatability in rare disorders [ 11 , 12 , 13 ], which is still underutilized, and only a few MPS centers make use of this, as shown by us previously [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Key hurdles, expressed by experts in our survey, included time and other efforts needed to plan and conduct the trials, as well as a lack of training in ITTs [ 22 ]. This is in line with other work that has shown that the know-how and efforts associated with profound RBAs needed to justify and plan ITTs are also key barriers in other fields [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITTs rely on the use of a treatment without scientifically proven efficacy or outside indications when established treatment methods are no longer helpful. Therefore, ITTs can be extremely useful for investigating new effects of care in diseases with unsatisfactory therapies [12].…”
mentioning
confidence: 99%